Subtle Esophageal Motility Alterations in Parkinsonian Syndromes: Synucleinopathies vs. Tauopathies. Issue 4 (15th May 2018) - Claus, Inga; Suttrup, Judith; Muhle, Paul; Suntrup‐Krueger, Sonja; Siemer, Marie‐Luise; Lenze, Frank; Dziewas, Rainer; Warnecke, Tobias
Abstract: Background: Esophageal dysfunction is a frequent phenomenon in Parkinson's disease during all disease stages, but data about esophageal involvement in atypical parkinsonian syndromes as well as possible differences between alpha‐synucleinopathies and tauopathies, including causative links to the origin of the dysfunction, are lacking so far. Objective: To describe esophageal alternation patterns in different parkinsonian syndromes and to look for differences supporting the hypothesis of alpha‐synuclein aggregation being linked to gastrointestinal impairment in parkinsonian syndromes. Methods: We performed an analysis and comparison of esophageal high‐resolution manometry examination parameters in n = 10 patients with Parkinson's disease, n = 10 patients with multiple system atrophy (both alpha‐synucleinopathies), n = 10 patients with progressive supranuclear palsy (tauopathy), and n = 10 age‐matched controls. Additionally, pharyngeal dysphagia was evaluated by an endoscopic examination of swallowing in all three patient groups. Results: Statistically significant lower values for esophageal peristalsis and distal contractile integral were found for both groups of alpha‐synucleinopathies (Parkinson's disease and multiple system atrophy) in comparison to the patients with tauopathy (progressive supranuclear palsy group), as well as the age‐matched controls, where pathological pharyngeal findings were similar in all patient groups. Conclusions: Subtle esophageal motility alterations in parkinsonian syndromes seem to be limited to alpha‐synucleinopathies, but are not measurable in tauopathies, indicating a causative connection between pathological alpha‐synuclein aggregation in gastrointestinal tissues and esophageal involvement.